Enhancing students' information literacy through project-based learning: A mini research on plant morphology identification - Neni Murniati; Y. Yennita; Dinda Triski Oktaria Ha; R. Riyanto (University of Muhammadiyah Malang, 2025)
Plant morphology courses develop students’ understanding of plant structures and identification skills through mini-research activities. Effective species identification requires a literature review and the ability to find, evaluate, and use relevant information. This qualitative study examines students’ information literacy skills in completing plant identification projects using Project-Based Learning (PjBL). The research involved 63 biology education students enrolled in a plant morphology course. Data were collected through questionnaires assessing information literacy skills and portfolios documenting mini-research reports. Descriptive analysis revealed that the PjBL model enhanced students’ information literacy skills, with 65% classified as